PELATIHAN PENGOPRASIAN APLIKASI KEUANGAN BERBASIS VBA MACRO EXCEL PADA IKM RENGGINANG DI DESA PRAMBONTERGAYANG KECAMATAN SOKO KABUPATEN TUBAN - Eko Wahyu; Faisal Ashari (UIN Sunan Kalijaga, 2023)
Prambontergayang Village, located in Soko District, Tuban Regency, is a village that is well known for the production of Rengginang snacks in the Soko sub-district. has the Urnika brand, the IRT has been established since 2015 and received PIRT (Household Industry Food) legality in 2018. The problems that occur with these IRTs are financial and bookkeeping management which are still carried out by recording in books or manually, repair solutions that offered is VBA Macro excel-based bookkeeping and finance training. The implementation method carried out in community service first examines the problems found in IRT by means of surveys to IRT locations, then examines solutions to these problems and is implemented with training. The results of community service are proven to be able to increase the productivity of IRT rengginang craftsmen in Prambonterga village, which is in Soko District, Tuban Regency, and IRT are able to independently manage finances well and improve time efficiency when reporting finances.